26.1k views
4 votes
I only need the answer to question B

I only need the answer to question B-example-1
User Orzechow
by
6.1k points

1 Answer

4 votes

Answer:

x=5

y=1

Explanation:

The substitution method is considered easier because of its simplification.

2x-3y=7 (1)

x+2y=7 (2)

considering equation (2),

x = 7 - 2y (3)

using the value of "x" in (1)

2 (7-2y) - 3y=7

14 - 4y- 3y = 7

14 - 7y = 7

7y = 14 - 7

7y = 7

y = 1 (4)

substituting this value of "y" in (3)

x = 7- 2(1)

x = 5

User Jwynveen
by
5.7k points